The Influence of Facade Elements on the Visual Quality of Colonial Buildings in Blitar City Based on Public Perception - Al Farisa, Zai Dzar; Santosa, Herry; Ernawati, Jenny (RUAS, 2025)
Blitar City is home to colonial-style architecture that serves as a symbol of the city's identity. However, the visual quality of many colonial building facades has deteriorated due to a lack of public attention. This study aims to identify the influence of facade elements on the visual quality of colonial building facades in Blitar City based on public perception. A novel approach is employed by integrating public perception through multiple linear regression analysis to advance previous studies on the same objects. The research adopts a descriptive quantitative approach, involving six selected colonial buildings based on architectural style and function: Blitar City KAI Station, Yonif Command Office House, Tugu Sri Lestari Hotel, St. Joseph's Church, Campus III PGSD UM, and Gebang Palace. The respondents involved in this study were 100 general public and 100 professionals who assessed facade elements such as form, color, roof, walls, doors, windows, and ornaments using a Likert scale of 1-5. The results reveal that ornaments significantly influence the overall visual quality of the building facades, while other elements show varying impacts depending on the building type. This study contributes to the preservation of colonial architecture and the development of heritage areas in Blitar City